Very Early Pulsed Dye Laser Intervention for Optimal Cosmetic Outcome in Post-Thyroidectomy Scars - Kim YH; Kim HS; Kim HK; Kim SY; Lee J; Kim YC; Park YJ (Dove Medical Press, 2024)
Yul Hee Kim,1 Han-Seul Kim,1 Hyeung Kyoo Kim,2 Soo Young Kim,2 Jeonghun Lee,2 You Chan Kim,1 Young Joon Park1 1Department of Dermatology, Ajou University School of Medicine, Suwon, Republic of Korea; 2Department of Surgery, Ajou University School of Medicine, Suwon, Republic of KoreaCorrespondence: Young Joon Park, Department of Dermatology, Ajou University Hospital, 164, World Cup-ro, Yeongtong-gu, Suwon-si, Gyeonggi-Do, Suwon, Republic of Korea, Tel +82-31-219-5187, Email aro@ajou.ac.krPurpose: Early intervention of surgical scars with a pulsed dye laser is known to effectively prevent pathologic scars. Despite multiple reports on the effectiveness of the treatment, very few studies have demonstrated its appropriate initiation timing. In this study, our objective was to determine the optimal timing for initiating laser treatment following thyroidectomy.Methods: This study retrospectively analyzed 91 patients undergoing pulsed dye laser treatment post-thyroidectomy, grouping them by treatment initiation timing. The patients underwent treatment at intervals of 3- 4 weeks with at least five sessions. Those with a high pliability score were injected with intralesional corticosteroids. The Antera 3D® skin imaging analyzer was used to assess biophysical parameters.Results: The total Vancouver Scar Scale score significantly reduced after treatment in all groups. The Vancouver Scar Scale score reduction rate was significantly higher after treatment in the group for which the treatment was initiated within 3 weeks of surgery. The pigmentation and erythema score analyzed by Antera 3D® was also lower in this group.Conclusion: Early intervention using a pulsed dye laser within 3 weeks of thyroidectomy can substantially inhibit pathological scar development, providing physicians with a guide for optimal treatment commencement.Keywords: hypertrophic scars, laser treatment of scar, scar, pulsed dye laser